Pédagogie et didactique à l'épreuve de la modernité - Yassine Zouari (Université de Provence, 2010)
In this article we study the connections between pedagogy and didactics regarded through the educative modernity metamorphoses. We intend to discover how modern pedagogies and the didactics of disciplines draw their rationalities from the modernity. Using an interpretative methodology, we attempt to validate the following hypothesis: even if pedagogy and didactics are inscribed in a rationalizing educational process consubstantial with modernity, each of these two approaches is subtended by a different predominant figure of modern reason, the praxeological rationality for pedagogy and the cognitive rationality for the didactics. That's how we can understand their diverging approaches of the sense of teaching practices.